2016
DOI: 10.1080/01902148.2016.1244578
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidinedithiocarbamate attenuates bleomycin-induced pulmonary fibrosis in rats: Modulation of oxidative stress, fibrosis, and inflammatory parameters

Abstract: PDTC attenuated bleomycin-induced pulmonary fibrosis in rats via its anti-inflammatory, antioxidant, and antifibrotic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…In our study, elevated hydroxyproline content in CBs‐treated lung tissues suggested that CBs could induce collagen synthesis. In agreement with our study, studies also suggested that there was a positive relation between hydroxyproline level and pathological grade of bleomycin‐induced pulmonary fibrosis 22 …”
Section: Discussionsupporting
confidence: 93%
“…In our study, elevated hydroxyproline content in CBs‐treated lung tissues suggested that CBs could induce collagen synthesis. In agreement with our study, studies also suggested that there was a positive relation between hydroxyproline level and pathological grade of bleomycin‐induced pulmonary fibrosis 22 …”
Section: Discussionsupporting
confidence: 93%
“…The hyperplasia of fibroblasts was increasingly evident with time and has been associated with chronic inflammatory reaction (21,22). Recent research has indicated that TNF-α and TGF-β1 promotes the development of inflammation and pulmonary fibrosis (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Bleomycin-induced pulmonary fibrosis in mice is a highly reproducible in vivo model to induce consistent pulmonary fibrosis. The bleomycin induces the production of free radicals by binding to iron and DNA and causes DNA, lipid, and protein damage, leading to the activation of inflammatory and fibrotic responses in the lung (20). Thus, we established a bleomycin-induced fibrosis model to evaluate the anti-fibrotic effect of morin.…”
Section: Discussionmentioning
confidence: 99%